H1‐Galerkin expanded mixed finite element methods for nonlinear pseudo‐parabolic integro‐differential equations. Issue 3 (13th June 2012) - Che, Haitao; Zhou, Zhaojie; Jiang, Ziwen; Wang, Yiju
Abstract H1‐Galerkin mixed finite element method combined with expanded mixed element method is discussed for nonlinear pseudo‐parabolic integro‐differential equations. We conduct theoretical analysis to study the existence and uniqueness of numerical solutions to the discrete scheme. A priori error estimates are derived for the unknown function, gradient function, and flux. Numerical example is presented to illustrate the effectiveness of the proposed scheme. © 2012 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq, 2013